Clinical outcomes of arthroscopic lateral ligament repair using a knotless anchor for chronic lateral ankle instability - Masashi Shimabukuro; Yuichi Hoshino; Noriyuki Kanzaki; Kiminari Kataoka; Tetsuya Yamamoto; Koji Nukuto; Kyohei Nishida; Kanto Nagai; Takehiko Matsushita; Ryosuke Kuroda (Elsevier, 2024)
Background/objective: Arthroscopic lateral ligament repair (ALLR) for chronic lateral ankle instability (CLAI) has been improving with technical innovations. However, there is a lack of information regarding mid- and/or long-term clinical outcomes after the introduction of ALLR. This study aimed to report mid-term clinical outcomes of ALLR with a knotless anchor. Methods: Thirty-two patients (11 men and 21 women; mean age, 28 ± 14 years) who underwent ALLR with a knotless anchor from December 2015 to October 2020 were included. The mean follow-up period was 31 ± 11 months. The Japanese Society for Surgery of the Foot (JSSF) ankle-hindfoot scale and the Self-Administered Foot Evaluation Questionnaire (SAFE-Q) were used for clinical evaluation preoperatively and at the 2-year follow-up. Surgical complications, particularly knot irritation, were also examined. Results: The JSSF scale scores were significantly improved, from 71.3 ± 13.1 preoperatively to 96.6 ± 5.1 postoperatively (P < 0.05), and the SAFE-Q showed similar improvement in all subscales (P < 0.05). One case had a complication of persistent pain around the lateral portal (3.1%). Conclusion: ALLR using a knotless anchor provided satisfactory clinical outcomes over 2 years, and no major complications, such as knot irritation, were observed. Case series: Level of Evidence, 4.